Adequacy of Outpatient Specialty Care Access in Marketplace Plans Under the Affordable Care Act. Issue 2 (February 2016) - Dorner, Stephen C.; Jacobs, Douglas B.; Sommers, Benjamin D.
Abstract : Obstet Gynecol Surv 2016;71(2):82–83 Nearly 12 million Americans are enrolled in health care coverage through the insurance marketplaces set up by the Affordable Care Act. Despite a "reasonable access" standard that has been applied to ensure access of covered individuals to specialty care, there are concerns about network adequacy.